Do Racial/Ethnic and Economic Factors Affect the Rate of Complicated Appendicitis in Children?. (29th June 2020) - Totapally, Abhinav; Martinez, Paul; Raszynski, Andre; Alkhoury, Fuad; Totapally, Balagangadhar R.
Abstract : Introduction . Appendicitis continues to be one of the most common surgical conditions in the pediatric population. We set out to determine demographic and practice variations among children admitted with appendicitis and highlight the racial/ethnic and healthcare access role in relation to the rate of complicated appendicitis using the 2012 Kids' Inpatient Database (KID). Methodology . A retrospective cross-sectional database study was performed using the 2012 KID. All children (age 1 months to 20 years) with appendicitis were identified using the ICD-9 diagnosis codes. Children with a diagnosis of appendicitis were compared with all other discharges. Among children with appendicitis, demographic and practice variations and the rate of complicated appendicitis were evaluated. Univariate and multivariate analyses were done to analyze the data. Sample weighing was done to present national estimates. Results . In 2012, a total of 89, 935 out of 2.7 million pediatric hospital discharges (3.3%) had a diagnosis of appendicitis. The incidence of appendicitis was higher in males (4.7%), 6–15-year age group (7.43%), Hispanics (5.2%), and in the Western region (5.2%) and was lower in infants (0.02%) and African American children (1.2%) (p < 0.0001 ). The proportion of children with peritonitis or abscess was higher in children's hospitals (48.2% vs. 29.0%; OR 2.3, 95% CI: 2.2–2.4). The risk of complicated appendicitis was inversely related to age, while racial and ethnic minority status, bottom quartile of the income group, and government insurance increased the risk. Laparoscopic appendectomy was performed more frequently at children's hospitals (84.8% vs. 74.3%; p < 0.0001 ). Conclusions . Appendicitis is more common in Hispanics, males, older children, and in the Western region. Complicated appendicitis is more common in younger children, minority groups, low-income group, and children with government insurance. Children's hospitals manage more children with complicated appendicitis and are more likely to perform laparoscopic appendectomy.